Plasticidade tecidual da junção miotendínea do sóleo de ratas Wistar idosas ovariectomizadas submetidas à natação - Sierra, Luan Rissatto [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The physiological process of aging results in several changes in the body systems where the resulting sarcopenia of muscle atrophy associated with menopause, several triggers morphological changes in muscle-tendon interaction area denominated myotendinous junction. Physical exercise may be result in benefits in the structure of myotendinous junction associated with a large increase in their contact area. The aim of this study is to analyze the tissue plasticity through the morphological analysis of myotendinous junction of the soleus in ovariectomized old Wistar rats submitted to swimming training. Will be used 40 rats aged with 1 year and 2 months old randomly divided into four groups (n = 10): Sedentary group; Trained group; Sedentary / Ovariectomized group and Trained / Ovariectomized group. The animals will be coming from the Central Animal Facility of UNESP - Botucatu-SP. The training protocol consist of 40 sessions, 1 hour daily, for a period of 8 weeks and loaded with 5% body weight of animals with weekly measurements for making adjustments. The obtained histological results will be analyzed by light microscopy, scanning electron microscopy and transmission electron microscopy, in order to demonstrate morphometric characteristics, three-dimensional aspects of structural and ultrastructural elements of the components at the cellular level. The results of this study showed the tissue plasticity of JMT the soleus of ovariectomized rats elderly. The statistical differences were presented in body mass values by making the protocol training and ovariectomy. Also highlighted were the broad sarcoplasmic projections from the tendon tissue and responsible for fixing to the muscle tissue. The three-dimensional aspects in structuring the JMT and its interaction with the dense connective tissue associated were revealed. the ultrastructural adaptations of ... (Complete abstract electronic access below)

O processo fisiológico do envelhecimento acarreta em diversas alterações aos sistemas corporais onde a sarcopenia resultante da atrofia muscular associado à menopausa, desencadeia diversas alterações morfológicas na área de interação músculo-tendão denominada de junção miotendínea. O exercício físico poderá acarretar em benefícios na estrutura da junção miotendínea associadas com um grande aumento em sua área de contato. O objetivo do presente estudo consistiu em analisar a plasticidade tecidual através da análise morfológica da junção miotendínea do sóleo em ratas Wistar idosas ovariectomizadas submetidas ao treinamento de natação. Foram utilizadas 40 ratas com 1 ano e 2 meses de idade divididas aleatoriamente em quatro Grupos, (n=10): Grupo Sedentário; Grupo Treinadas; GrupoSedentário/Ovariectomizadas e Grupo Treinadas/Ovariectomizadas. Os animais foram oriundos do Biotério Central da UNESP - Campus de Botucatu-SP. O protocolo de treinamento consistiu em 40 sessões, durante uma hora diária, por um período de oito semanas e sobrecarga de 5% da massa corporal dos animais, com mensuração semanal para realização de ajustes. As imagens histológicas obtidas foram analisadas através da microscopia de luz, microscopia eletrônica de varredura e microscopia eletrônica de transmissão, de maneira a evidenciar características morfométricas, aspectos tridimensionais dos elementos estruturais e ultraestruturais dos componentes ao nível celular. Os resultados do presente estudo evidenciaram a plasticidade tecidual da JMT do sóleo de ratas idosas ovariectomizadas. Foram apresentadas as diferenças estatísticas nos valores de massa corporal mediante a realização do protocol de treinamento e ovariectomia. Além disso foram evidenciadas as amplas projeções sarcoplasmáticas provenientes do tecido tendíneo ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Envelhecimento; Junção neuromuscular; Menopausa; Exercícios físicos